A Coalition and Synthesis of Published Health Research in the Journal of Military, Veteran, and Family Health - Paige Bain; Nicholas Held (Inquiry@Queen's Undergraduate Research Conference Proceedings, 2026)
A central role of the Canadian Institute for Military and Veteran Health Research (CIMVHR) is knowledge mobilization, the process of translating research to inform policy, practice, and communities. The Journal of Military, Veteran, and Family Health (JMVFH) is one approach CIMVHR uses to mobilize peer-reviewed evidence to interested partners. Although JMVFH publishes lay summaries, its digital infrastructure presents navigation challenges and barriers to knowledge translation, dissemination, and implementation. This project aims to address these barriers through a systematically designed review, categorization, and synthesis of the JMVFH archive to enhance knowledge mobilization. It employed evidence mapping to develop a taxonomy for the full body of literature through iterative coding. The sample consisted of 530 JMVFH publications, each was reviewed and key exposures, outcomes, and implications were recorded as terms. This process yielded a total of 257 keywords, which were subsequently organized into 135 subcategories and 36 categories to characterize the topical landscape of the archive. Following a series of AI experiments, training documents and workflows were developed and enforced in code to power the Bridging Evidence for Armed forces Communities and Operational Needs (BEACON) agent. BEACON facilitates automated taxonomy classification for new publications, archives their metadata, and indexes the JMVFH database to generate summaries at the subcategory- and category-level. Additionally, BEACON offers a comprehensive framework for further development and integration into the digital infrastructure at CIMVHR. Beyond its utility for the academic community, BEACON facilitates evidence synthesis that captures the dynamic nature of health research and packages it in an accessible format. Ultimately, the patient-centred design streamlines resource navigation and enhances the delivery of emerging research to support and protect the health of military-connected populations.Faculty Supervisors: Dr. Steven Smith, Dr. Nicholas Held